1999
DOI: 10.1523/jneurosci.19-13-05255.1999
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Inactivation of Ca2+- and Voltage-Dependent BK Channels in Adrenal Chromaffin Cells and Rat Insulinoma Tumor Cells

Abstract: Large-conductance Ca 2ϩ -and voltage-dependent potassium (BK) channels exhibit functional diversity not explained by known splice variants of the single Slo ␣-subunit. Here we describe an accessory subunit (␤3) with homology to other ␤-subunits of BK channels that confers inactivation when it is coexpressed with Slo. Message encoding the ␤3 subunit is found in rat insulinoma tumor (RINm5f) cells and adrenal chromaffin cells, both of which express inactivating BK channels. Channels resulting from coexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
423
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(439 citation statements)
references
References 44 publications
15
423
0
Order By: Relevance
“…BK channels are noninactivating K + channels, except in the presence of a β2 or β3 auxiliary subunit whose N-terminal peptide sequence occludes the channel pore in a more N-type inactivation manner (31)(32)(33). We found that, even under nearly K + -free conditions in the external recording solution, WT BK channels did not show any significant inactivation up to 10 s. The presence of Tyr at the BK channel 294 position (equivalent to the 449 position in Shaker channels) might partly contribute to the noninactivation because the T449Y mutation slows down C-type inactivation in Shaker channels (25).…”
Section: Discussionmentioning
confidence: 99%
“…BK channels are noninactivating K + channels, except in the presence of a β2 or β3 auxiliary subunit whose N-terminal peptide sequence occludes the channel pore in a more N-type inactivation manner (31)(32)(33). We found that, even under nearly K + -free conditions in the external recording solution, WT BK channels did not show any significant inactivation up to 10 s. The presence of Tyr at the BK channel 294 position (equivalent to the 449 position in Shaker channels) might partly contribute to the noninactivation because the T449Y mutation slows down C-type inactivation in Shaker channels (25).…”
Section: Discussionmentioning
confidence: 99%
“…They are negative feedback regulators of cellular excitability and of [Ca 2ϩ ] i . BK channels are a complex of four ␣-subunits (1) and four ␤-subunits (2)(3)(4)(5)(6)(7). In addition to the S1-S6 transmembrane (TM) helices conserved in all voltage-gated K ϩ channels, ␣ contains a unique seventh TM helix, S0, N-terminal to S1-S6; furthermore, the first 19 residues preceding S0 are extracellular (Fig.…”
mentioning
confidence: 99%
“…Their binding to the channel is altered by the association of ␤ subunits; ␤1 enhances the binding affinity of ChTx (37) but reduces the sensitivity of the current to IbTx (38), whereas ␤2 and ␤4 reduce sensitivity to ChTx and IbTx inhibition (8,26). Experimental evidence suggests that these effects are mediated by the extracellular loop of the ␤ subunits that extends to the extracellular vestibule of the pore (26,37,39). Similar to ChTx and IbTx, ␤4 reduced inhibition by slotoxin (40).…”
Section: Discussionmentioning
confidence: 99%